MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD SWASTA AL-WASHLIYAH BERASTAGI - Yunistita, Yunistita; Br Sembiring, Egidia Putri Buluh Duri (Universitas Quality, 2024)
The difficulties experienced by fourth grade students at Al-Washliyah Berastagi Private Elementary School in the Indonesian language subject are proven by the percentage of student learning in the class of 43% of students completing. The cause is the use of learning models that are rarely used resulting in low student learning outcomes, students are less active in the learning process because the learning process is still teacher-centered, students' learning attitudes are boring, and teachers rarely use media during learning. This type of research is classroom action research (PTK) which aims to find out how learning is implemented, how complete student learning outcomes are and whether student learning outcomes improve. The model in this research uses the Suharsimi Arikunto research model which consists of 4 stages, namely; planning, implementation, observation, reflection. The subjects of this research were fourth grade students at Al-Washliyah Berastagi Private Elementary School with a total of 21 students, consisting of 7 male students and 14 female students. Data collection techniques use teacher and student observation sheets, a 5-question multiple choice test and documentation. The results of the research are as follows: The results of teacher activities reached a percentage of 87.3% (very good). The results of student activities reached 92 (very good). The results of individual and classical completion were 19 students with a percentage of 90.4% who completed their studies. The average student learning result reached a score of 90. The percentage increase in student learning outcomes for cycle I and cycle II reached a percentage of 16.8%. Based on the results of the research above, it can be concluded that by using the Contextual Teaching And Learning learning model, the implementation of learning criteria is very good, the learning outcomes are classically complete and improved in Class IV Indonesian Language Subjects at Al-Washliyah Berastagi Private Elementary School for the 2022/2023 Academic Year.